A pintura de Regina Chulam como experiência sensível - Mies, Jorge Luiz (2014)
This dissertation investigates the praxis of capixaba painter Regina Chulam, from 1975, when she started studying in London and also working with Fine Arts, until 2013, when she organized her first solo exhibition at Museu Vale, in Vila Velha, Espírito Sa